2023
DOI: 10.1186/s40635-023-00528-0
|View full text |Cite
|
Sign up to set email alerts
|

Serum proteome profiles in patients treated with targeted temperature management after out-of-hospital cardiac arrest

Abstract: Background Definition of temporal serum proteome profiles after out-of-hospital cardiac arrest may identify biological processes associated with severe hypoxia–ischaemia and reperfusion. It may further explore intervention effects for new mechanistic insights, identify candidate prognostic protein biomarkers and potential therapeutic targets. This pilot study aimed to investigate serum proteome profiles from unconscious patients admitted to hospital after out-of-hospital cardiac arrest accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…Going a step further, we identified 2 proteins, NGAL and angiotensinogen, that were also significantly differentiated in the comparison between good and poor neuroprognostication in human serum proteomic studies at 24 hours after ROSC. 28 The expression level and spatial expression characteristics of NGAL (Figure 6C through 6E) and CD14 (Figure S5) in brain were examined by immunofluorescence. We found the cerebral expression of NGAL was extremely low in the sham-operated mice (Figure 7C), and increased expression were found after CA/CPR (Figure 7D and 7E).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Going a step further, we identified 2 proteins, NGAL and angiotensinogen, that were also significantly differentiated in the comparison between good and poor neuroprognostication in human serum proteomic studies at 24 hours after ROSC. 28 The expression level and spatial expression characteristics of NGAL (Figure 6C through 6E) and CD14 (Figure S5) in brain were examined by immunofluorescence. We found the cerebral expression of NGAL was extremely low in the sham-operated mice (Figure 7C), and increased expression were found after CA/CPR (Figure 7D and 7E).…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, it is scarcely possible to obtain brain samples for protein detecting in clinical practice, and serum is the most widely used and most accessible sample for detection of prognostication. Previous clinical studies have shown the serous detectability of NGAL and angiotensinogen, 28 and a further challenge is focusing on the cerebral-specific quantification of release of these biomarkers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We applied a 70% rule to filter missing values, retaining only analytes identified in at least 70% of samples. Our decision aligns with the original publications and common practices in proteomics, where researchers often opt for filtering strategies without imputation to handle missing values ( Yang et al 2015 , De Marchi et al 2016 , Messner et al 2020 , Hristova et al 2023 , Lileikyte et al 2023 ). Gene ontology enrichment analysis was performed using the enrichGO function() in the clusterProfiler R package ( Yu et al 2012 , Wu et al 2021 ).…”
Section: Methodsmentioning
confidence: 90%
“…A recent study of serum samples collected from Swedish patients enrolled in the targeted temperature management (TTM) trial has identified additional, potential biomarkers through proteomic analysis [ 52 ]. Comparing patients with good and poor neurological outcome 6 months following CA, the study proposed the utility of proteins known to be implicated in immune programs, including kallistatin and angiotensinogen, in neuroprognostication and treatment monitoring.…”
Section: Prognostic Assessment Of Post-cardiac Arrest Outcomes Throug...mentioning
confidence: 99%